Sexual and reproductive health communication intervention for caretakers of adolescents: a quasi-experimental study in Unguja- Zanzibar - Saada A. Seif; Thecla W. Kohi; Candida S. Moshiro (BMC, 2019)
Abstract Background Caretakers/parents or parents figure need to be trained to promote effective communication about sexual and reproductive health to their adolescents. This study assessed the effect of an intervention aiming to improve caretaker-adolescent communication on sexual and reproductive health matters through improving information, motivation, and behavioral skills related to sexual health communication. The study also evaluated the relationship of information, motivation, and behavioral skills model-constructs with communication practice. Information-Motivation-Behavioural skills model was used as a framework to guide the intervention implementation and evaluation process. Method This is a quasi-experimental non-randomized controlled pre- and post-test study which involved one thousand caretakers of adolescents in all the six districts of Unguja-Zanzibar. All participants completed interviewer-administered structured pre-test questionnaire. The experimental group then received sexual health communication intervention addressing the information, motivation, and behavioral skills related to sexual health communication, while the control group received the sexual health information only. All participants were then reassessed for their information, motivation, behavioral skills and their sexual health communication after 1 month, 6 months and at 1 year following the intervention. To evaluate the effect of intervention at the post-test measures, Univariate Analyses of Covariance was performed whereby the pre-test score and variables on which the groups differed were considered as covariates. Standardized mean difference statistics of Cohen's d was used to calculate the effect size, and the cut-off point for the level of significance was set at two-sided, p-value < 0.05. Results Results shows that the immediate post-test sexual health communication, motivation and behavioral skills scores were statistically significantly higher in the experimental group compared to control group (p < 0.05). Moreover, sexual health communication score after 6 months and at 1 year were statistically significantly higher in the experimental group compared to control group (p < 0.05). Information construct however did not differ between groups in post-test measures. Furthermore, results revealed that communication practice is statistically significantly associated with information, motivation and behavioural skills in post-test measures. Conclusion The findings provided preliminary evidence for the effectiveness of SRH communication intervention and supported the significance of IMB model-constructs to inform the SRH-communication intervention and to guide the intervention evaluation.